Voltage-sensing phosphatase modulation by a C2 domain - Castle, Paul M.; Zolman, Kevin D.; Kohout, Susy C. (Frontiers in Pharmacology, 2015)
The voltage-sensing phosphatase (VSP) is the first example of an enzyme controlled by changes in membrane potential. VSP has four distinct regions: the transmembrane voltage-sensing domain (VSD), the inter-domain linker, the cytosolic catalytic domain and the C2 domain. The VSD transmits the changes in membrane potential through the inter-domain linker activating the catalytic domain which then dephosphorylates phosphatidylinositol phosphate lipids. The role of the C2, however, has not been established. In this study, we explore two possible roles for the C2: catalysis and membrane-binding. The Ci-VSP crystal structures show that the C2 residue Y522 lines the active site suggesting a contribution to catalysis. When we mutated Y522 to phenylalanine, we found a shift in the voltage dependence of activity. This suggests hydrogen bonding as a mechanism of action. Going one step further, when we deleted the entire C2 domain, we found voltage-dependent enzyme activity was no longer detectable. This result clearly indicates the entire C2 is necessary for catalysis as well as for modulating activity. As C2s are known membrane-binding domains, we tested whether the VSP C2 interacts with the membrane. We probed a cluster of four positively charged residues lining the top of the C2 and suggested by previous studies to interact with phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) (Kalli et al., 2014). Neutralizing those positive charges significantly shifted the voltage dependence of activity to higher voltages. We tested membrane binding by depleting PI(4,5)P2 from the membrane using the 5HT2C receptor and found that the VSD motions as measured by voltage clamp fluorometry were not changed. These results suggest that if the C2 domain interacts with the membrane to influence VSP function it may not occur exclusively through PI(4,5)P2. Together, this data advances our understanding of the VSP C2 by demonstrating a necessary and critical role for the C2 domain in VSP function.